Exploring influential factors in the self-assessment of life satisfaction among Chinese elderly: a structural equation modeling analysis - Yan, Jun; Wang, Suzhen; Liu, Chang; Lu, Yuanan (Frontiers in Psychiatry, 2024)
The aging problem is becoming more and more prominent globally. Attention on the quality of life of the elderly and related health improvement have become an important issue in modern society. To explore the factors influencing the self-assessment of life satisfaction of the elderly, a Health Influencing Factors Tracking Survey was conducted between 2017-2018 with 9,327 participants of the Chinese Elderly. Analysis of the influencing factors of the self-assessment of life satisfaction of the elderly in different regions of China (cities, towns, and villages) was carried out by using structural equation modeling. This study revealed that economic status, psychological status, personal situation, life behaviors, and child care are important influences on older people's selfassessed life satisfaction. There is a positive correlation between economic status, psychological status, child care and the results of the self-assessment of life satisfaction of the elderly. Psychological status and child care of the elderly in urban areas have a higher impact on the self-assessment of life satisfaction of the elderly than in villages and towns.The influence of economic status on the self-assessment of life satisfaction of the elderly is lower in urban areas than in rural areas. There is a significant difference in the influence of personal situation on the self-assessment of life satisfaction of the elderly, in which the older the elderly the higher the level of self-assessment of life satisfaction, and the selfassessment of life satisfaction of female elderly is higher than that of male. Findings from this study indicate that improving health self-assessment in older adults requires targeted efforts based on different geographic areas of life and the age stages of older adults, and more attention needs to be paid to men who are just entering old age.